EMOTIONAL INTELLIGENCE AND ACADEMIC ACHIEVEMENT AMONG UNIVERSITY UPGRADING (GRADE V) TEACHER STUDENTS - Amongin Waiswa, Helen Christine; Baguma, Professor Peter K.; Oonyu, Associate Professor Joseph (African Journal of Education and Practice, 2020)
Purpose: The study investigated the relationship between Emotional Intelligence (EI) and Achievement (AA) among Upgrading University Teacher Students at Makerere University and Uganda Christian University, Mukono. EI that started to gather attention from the 1920s from the time of Thorndike, has become a very vital part of everyday living, involving names like Mayer, Salovey, Goleman, and Bar-On. The curricula and syllabi in the Teacher Education programmes in Uganda do not clearly stipulate EI as a vital and critical contributor. The Report of the Visitation Committee to Public Universities and National Council for Higher Education Report of 2013 suggested that teacher students were generally performing reasonably well academically, but it did not say anything about the contribution of EI in their achievement. Methodology: Using mixed methodology, and DCM SPSS 22 data analysis, a sample of 434 teacher students purposively selected. Results: The ability model of Emotional Intelligence, emotional awareness (r = .22, p < .001), ability to generate and use emotions, and emotional knowledge were found to be significantly related to subjective achievement (r = .21, p < .001), and emotional knowledge (r = .22, p < .001), were significantly related to subjective achievement. Only emotional management was not significantly related to subjective achievement (r = 19, p < .01). Qualitative data corroborated these findings. However, all aspects of emotional intelligence were not related to objective achievement (CGPA). Regression analysis confirmed the same results. The study concluded that Emotional awareness, Ability to generate emotions, Emotional knowledge, and Emotional management have a positive significance with subjective AA. Unique contribution to theory, policy and practice: EI contributes to and enhances cognitive abilities in students. Attribution and emotional intelligence theories contribute to academic achievement. It is recommended that EI be taught at all levels of the educational system.